THE SOCIAL FUNCTIONING OF WOMEN WITH BREAST CANCER IN THE CONTEXT OF THE LIFE WORLD: A SOCIAL WORK PERSPECTIVE - van Wyk, Jonita; Carbonatto, Charlene (Social Work/Maatskaplike Werk, 2016)
Breast cancer is the most common form of cancer in women worldwide (CANSA, 2010). The goal of this study was to explore the social functioning of women with breast cancer. A qualitative research approach was followed with a collective case study research design. In this study non-probability, purposive sampling was used to select participants. One of the themes generated was the impact of breast cancer on social functioning in the context of the life world. This theme includes changes in personality; feeling like a woman; changes in spiritual aspects; and self-image. Research showed that there were mainly positive changes experienced.